Incidence and risk factors for abdominal occult metastatic disease in patients with pancreatic adenocarcinoma. Issue 8 (31st October 2018) - Gemenetzis, Georgios; Groot, Vincent P.; Blair, Alex B.; Ding, Ding; Thakker, Sameer S.; Fishman, Elliot K.; Cameron, John L.; Makary, Martin A.; Weiss, Matthew J.; Wolfgang, Christopher L.; He, Jin
Abstract : Background: The incidence of occult metastatic disease (OMD) in pancreatic ductal adenocarcinoma (PDAC) and associated risk factors are largely unknown. Methods: We identified all patients with PDAC, who had an aborted oncologic operation due to OMD within a 10‐year period. The cases were matched to a cohort of resected PDAC patients on a 1:3 ratio, based on age and sex, for comparison of preoperative clinical characteristics and potential risk factors for OMD. Results: In the studied period, 117 patients with OMD were identified in 1423 pancreatectomies performed for PDAC (8%). Liver metastases were the most common finding (79%) followed by peritoneal implants (16%). When compared with non‐OMD cases, patients with OMD presented more often with abdominal pain ( P  < 0.001), and higher preoperative carbohydrate antigen 19‐9 (CA 19‐9) values ( P  = 0.007). Additionally, indeterminate liver lesions on preoperative computed tomography (CT) were identified in 40% of OMD versus 17% of non‐OMD patients ( P  < 0.001). Multivariable analysis distinguished four independent predictors for OMD: indeterminate lesions on preoperative CT, tumor size > 30 mm, abdominal pain, and preoperative CA 19‐9 > 192 U/mL. Conclusions: Occurrence of OMD in PDAC accounts for 8% of cases. Preoperative CA 19‐9 > 192 U/mL, primary tumor size > 30 mm, and identification of indeterminate lesions in preoperative CT may indicate the need for diagnostic laparoscopy.